2012
DOI: 10.1103/physrevlett.108.066405
|View full text |Cite
|
Sign up to set email alerts
|

Single-Ion Kondo Scaling of the Coherent Fermi Liquid Regime inCe1xLaxNi2Ge2

Abstract: Thermodynamic and transport properties of the La-diluted Kondo lattice CeNi2Ge2 were studied in a wide temperature range. The Ce-rich alloys Ce1−xLaxNi2Ge2 were found to exhibit distinct features of the coherent heavy Fermi liquid. At intermediate compositions (0.7 x 0.9) nonFermi liquid properties have been observed, followed by the local Fermi liquid behavior in the dilute limit. The 4f -electron contribution to the specific heat was found to follow the predictions of the Kondo impurity model both in the loc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 26 publications
4
29
0
Order By: Relevance
“…2. Such a concurrence of T K and T coh has already been stated for CeCu 2 Si 2 [17] as well as the isostructural HF metals YbRh 2 Si 2 [18] and CeNi 2 Ge 2 [19]. For comparison, we also present results on the nonmagnetic reference compound LaCu 2 Si 2 .…”
supporting
confidence: 76%
See 1 more Smart Citation
“…2. Such a concurrence of T K and T coh has already been stated for CeCu 2 Si 2 [17] as well as the isostructural HF metals YbRh 2 Si 2 [18] and CeNi 2 Ge 2 [19]. For comparison, we also present results on the nonmagnetic reference compound LaCu 2 Si 2 .…”
supporting
confidence: 76%
“…In conclusion, we showed that the enhanced TEP as well as the Nernst coefficient of the [19]. Our results indicate the Nernst effect to be a promising probe for directly detecting asymmetric scattering processes in correlated-electron systems and, therefore, to play an important role in exploring unconventional thermoelectric materials for potential applications.…”
mentioning
confidence: 54%
“…29 Owing to the absence of magnetism in the Ni sublattice, the Ce-Ni-based compounds have shown great advantage in studying the Ce-4f -electron correlation. 14,33,37,38 This also accounts to the fact that the CaBe 2 Ge 2 -type CeNi 2 As 2 is a nonmagnetic Kondo lattice because the Kondo coupling is largely enhanced by one of the inverted NiAs layer. Compared with all these cases, the ThCr 2 Si 2 -type CeNi 2 As 2 has a relatively small Kondo coupling but a moderately strong magnetic frustration.…”
Section: Resultsmentioning
confidence: 95%
“…It can be described in terms of the Schotte-Schotte model [19]. It was argued before that such model applies even in a Kondo lattice regime: [20]. The second, broad peak is located roughly at 22 K. According to our knowledge, it is related to crystal field effects, described by the modified Schottky formula [21].…”
Section: Specific Heatmentioning
confidence: 86%